Contextual Learning of Civic Education Based on Islamic Values for Islamic Elementary School Children - Saleh, Syarbaini; Nur, Abdurrabbani Usman (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
The research developed a contextual learning model for Islamic values-based civic education. The research tested the validity, development of religious attitudes, and measured the model's effectiveness on learning outcomes. The research used an ERD by adopting Plomp. The research presented the product research results in the form of a contextual learning model book based on Islamic values for civic education as a learning aid to implement the learning model. The ERD covered 12 MIN in Medan City. The instruments used in this research were: (1) model validation sheet; (2) observation sheet; and (3) learning outcome test. The ERD showed that the contextual learning model book for Islamic values-based civic education was declared valid with an average score of 3.26 for each aspect and was suitable for testing in large groups. Meanwhile, after testing its feasibility, it was necessary to test the contextual learning model for Islamic values-based civic education in fostering students' religious attitudes with an average of 3.27. Meanwhile, the model's effectiveness showed a moderate category with an N-Gain value of 0.55 on student learning outcomes. ERD shows that contextual learning based on Islamic values can be developed, fostering students' religious attitudes and effectively improving learning outcomes.